Role of Chemical Potential in Flake Shape and Edge Properties of Monolayer MoS2 - Cao, Dan; Shen, Tao; Liang, Pei; Chen, Xiaoshuang; Shu, Haibo (Journal of physical chemistry. C, 2015)
The precise control of the edge geometry and crystal shape of monolayer MoS2 is of particular importance for their application in nanoelectronics and photoelectro catalysts. Here, we reveal a crucial role of chemical potential in the determination of equilibrium shape (ES) and edge structure of monolayer MoS2 by using density-functional theory calculations. Applying the Wulff construction rule, our results demonstrate the shape evolution of monolayer MoS2 flake from the dodecagonal shape, then to the hexagonal shape, to the triangular shape with the variation of chemical potential from the Mo-rich to the S-rich condition, and the edge structure of ES changes correspondingly from mixed zigzag/armchair edges to purely zigzag edges. This finding can be applied to explain extensive experimental observations about the morphology of MoS2 domains. Likewise, the edge magnetism and electronic structures of monolayer MoS2 domains are found to be dependent on their edge structure, which provides specific guidance for the magnetic modulation of monolayer MoS2 and the design of more effective MoS2-based catalysts.